Proton Beam Stereotactic Radiosurgery for Pediatric Cerebral Arteriovenous Malformations. Issue 4 (19th March 2014) - Walcott, Brian P.; Hattangadi-Gluth, Jona A.; Stapleton, Christopher J.; Ogilvy, Christopher S.; Chapman, Paul H.; Loeffler, Jay S.
ABSTRACT: BACKGROUND: For cerebral arteriovenous malformations (AVMs) determined to be high risk for surgery or endovascular embolization, stereotactic radiosurgery (SRS) is considered the mainstay of treatment. OBJECTIVE: To determine the outcomes of pediatric patients with AVMs treated with proton SRS. METHODS: We reviewed the records of 44 consecutively treated pediatric patients (younger than 18 years of age) who underwent proton SRS at our institution from 1998 to 2010. The median target volume was 4.5 ± 5.9 mL (range, 0.3-29.0 mL) and the median maximal diameter was 3.6 ± 1.5 cm (range, 1-6 cm). Radiation was administered with a median prescription dose of 15.50 ± 1.87 CGE to the 90% isodose. RESULTS: At a median follow-up of 52 ± 25 months, 2 patients (4.5%) had no response, 24 patients (59.1%) had a partial response, and 18 patients (40.9%) experienced obliteration of their AVM. The median time to obliteration was 49 ± 26 months, including 17 patients who underwent repeat proton radiosurgery. Four patients (9%) experienced hemorrhage after treatment at a median time of 45 ± 15 months. Univariate analysis identified modified AVM scale score ( P = .045), single fraction treatment (0.04), larger prescription dose (0.01), larger maximum dose (<0.001), and larger minimum dose (0.01) to be associated with AVM obliteration. CONCLUSION: High-risk AVMs can be safely treated with proton radiosurgery in the pediatric population. Because protons deposit energy more selectively than photons, there is the potential benefit of protons to lower the probability of damage to healthy tissue in the developing brain.